LECTIN RECEPTORS IN THE STRUCTURAL COMPONENTS OF THE RAT EYE BALL UNDER CONDITIONS OF L-THYROXINE EFFECT - Shchur, M.B.; Yashchenko, A.M. (World of Medicine and Biology, 2016)
To study the carbohydrate determinants of functional apparatus of the eyeball a set of lectins of different carbohydrate specificity, labeled with horseradish peroxidase, was used: LABA (αL-Fuc), PNA (βDGal), WGA (NAcDGlc Na Na), HPA (αNAcDGal), SNA (NeuNAc (α2-6) DGal) and CNFA (GalNAcβ1). Lectins SNA, PNA, HPA, CNFA, LABA showed high binding specificity in corneal stroma with keratocytes of both – control and experimental groups. The abovementioned is probably caused by high degree of glycosylation in the Golgi membranes involving the carbohydrate components such as βDGal, αNAcDGal, αL-Fuc, NAcDGlc and by their production of keratan sulfate, which supports the hydration of the cornea. SNA and LABA lectins may be recommended as the selective histochemical markers of multipolar neurons of ganglion cell layer, WGA lectin may be proposed for differential detection of horizontal and amacrine cells. Perspectives for further research. In the future the functional apparatus of the eyeball will be investigated on semithin sections using a larger panel of lectins.